THE INFLUENCE OF SERVICE QUALITY, PERCEIVED VALUE AND CORPORATE IMAGE TOWARD INPATIENT SATISFACTION ON PRIVATE HOSPITAL - Novella, Selly; Polla, Johannes Ronaldy; Dharma, Octa Marihot; Walia, Puspa (Social Economics and Ecology International Journal, 2018)
The purpose of this research was to determine the influence of service quality, perceived value, and corporate image of the hospital toward inpatient satisfaction of private hospitals in Jabodetabek.  This study is categorized as a survey research, where researchers distributed questionnaires to 155 respondents who had been inpatients in private hospitals in Jabodetabek area. The method that used in this research is quantitative method and descriptive analysis. The method used in this research is simple and multiple linear regressions using SPSS v20. The results of this research showed that service quality, perceived value, and corporate image of Private Hospitals in Jabodetabek have significantly affect patient satisfaction on private hospitals in Jabodetabek.